A novel design of low carbon footprint Ultra-High Performance Concrete (UHPC) based on full scale recycling of gold tailings. (18th October 2021) - Wang, J.N.; Yu, R.; Xu, W.Y.; Hu, C.Y.; Shui, Z.H.; Qian, D.; Leng, Y.; Liu, K.N.; Hou, D.S.; Wang, X.P.
Highlights: A low carbon footprint Ultra-High Performance Concrete (UHPC) is developed. The idea of full scale recycling is proposed to reuse gold tailings. The macro properties of the developed UHPC are evaluated. The microstructure of the developed UHPC is presented. The environmental characteristics of the developed UHPC are assessed. Abstract: This paper presents a feasible way to design a low carbon footprint Ultra-High Performance Concrete (UHPC) with gold tailings based on the idea of full scale recycling. Due to the fact that the particle size distribution of the recycled gold tailings is normally wild, from micrometer to millimeter, it could be utilized to replace powders and aggregates in UHPC simultaneously, which can get rid of sieving process and improve the recycling efficiency. Therefore, in this study, a particle dense packing model is firstly employed to design the UHPC matrix with gold tailings, based on the full scale recycling point of view. Then, the fresh and hardened properties of the newly developed UHPC are investigated, including flowability, compressive strength, hydration kinetics, durability and microstructure. The tested results indicate that the idea of full scale recycling can guarantee a relatively high long-term compressive strength, low DRCM, and low leaching toxicity for UHPC. Additionally, the environmental evaluation further proves that the developed UHPC is a green building material with advanced properties and simple preparation process.